Where I Come From: Exploring Regional Differences in California Consumers’ Attitudes and Beliefs About Fluid Milk - Annie R. Specht; Ashlan E Wickstrom; Emily B. Buck (Journal of Applied Communications, 2017)
Guided by the theory of reasoned action and social cognitive theory, this study was conducted to better understand how decisions to purchase organic or conventional milk are influenced by norms and attitudes established via human interactions and how those norms and attitudes vary by geographic region. An online Qualtrics survey was used to gain insight into behaviors, attitudes, and interactions of 308 milk consumers in various geographical regions of [State]. The findings indicate that urban, suburban, and rural consumers differ in some ways in their interactions related to milk information, as well as their perceptions of organic versus conventional milk. Based on the findings of the study, differences in personal networks and exposure to certain messaging in varying regions might perpetuate a more positive, confident, and informed view of organic or conventional milk products in some areas more so than others. The researchers recommend using the results of the study to tailor messages to the specific information needs of consumers in urban, suburban, and rural regions of [State].
Keywords: Theory of planned behavior; social cognitive theory; dairy; marketing; networks